Efektivitas Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Di Desa Banjarsari Kecamatan Sukatani Kabupaten Bekasi Tahun 2017-2023 - Dahuri, Adin; Yani, Yani (Jurnal Ilmu Administrasi Publik, 2024)
The research is descriptive with qualitative approach. The research concerns on the collection   effectiveness of Land and Building of Rural and Urban Tax (PBB-P2) of Banjarsari Sub District in 2017-2023. Data of tax achievement obtained from Departmen of Tax in Sukatani District and information relating to the research collected by interviewing tax collector as well as some residents of Banjarsari Sub Dictrict of Bekasi Regency. The result of the reseach that the achievement of PBB-P2 revenue during 2017-2023 ranged from 35% to 67% or an average achievement of 46,86% per year. These achievements showed that the efforts to collect PBB-P2 revenue during that period were ineffective because the realization of PBB-P2 revenues did not reach predetermined targets. The ineffectiveness PBB-P2 collection is due to some obsracles, such as the obedience of some tax payers which continuosly to be encouraged, lack of officers which being very disproportionate to the number of   tax payers, as well as ineffective the use of "Sapa Bekasi" application for online payment. To increase PBB-P2 revenue for the following years, the Banjarsari Sub District government needs to make some improvements, such as providing an undestanding of the impotance of paying PBB-P2 to financing the necessities of local goverment,   involving and   collaborating with RW and RT administrators to support tax collector, and practising the use of "Sapa Bekasi" application to pay online